Beneficial Effects of Prebiotic Saccharomyces cerevisiae Mannan on Allergic Asthma Mouse Models - D. Betty Lew; Christie F. Michael; Tracie Overbeck; W. Scout Robinson; Erin L. Rohman; Jeffrey M. Lehman; Jennifer K. Patel; Brandi Eiseman; Kim S. LeMessurier; Amali E. Samarasinghe; M. Waleed Gaber (Journal of Immunology Research)
One of the unmet needs for asthma management is a new therapeutic agent with both anti-inflammatory and anti-smooth muscle (ASM) remodeling effects. The mannose receptor (MR) family plays an important role in allergen uptake and processing of major allergens Der p 1 and Fel d 1. We have previously reported that ASM cells express a mannose receptor (ASM-MR) and that mannan derived from Saccharomyces cerevisiae (SC-MN) inhibits mannosyl-rich lysosomal hydrolase-induced bovine ASM cell proliferation. Using a humanized transgenic mouse strain (huASM-MRC2) expressing the human MRC2 receptor in a SM tissue-specific manner, we have demonstrated that ASM hyperplasia/hypertrophy can occur as early as 15 days after allergen challenge in this mouse model and this phenomenon is preventable with SC-MN treatment. This proof-of-concept study would facilitate future development of a potential asthma therapeutic agent with dual function of anti-inflammatory and anti-smooth muscle remodeling effects.